Food Influencers in Egypt: The Emergence of Digital Trendsetters and the Cultural Glorification of Food - Behera, Kunmun Sahu (Journal of Global Economy, Business and Finance, 2026)
This exploratory study examines the role of food influencers in Egypt, focusing on their impact on audience perceptions and consumption habits. Drawing upon recent literature and theoretical models such as the Source Credibility Theory, the study identifies how food influencers shape consumer behavior and digital marketing trends. The research also highlights the phenomenon of food glorification, where influencers elevate food beyond mere sustenance, contributing to changing societal attitudes toward dining culture. The findings provide a foundation for future research into the ethical and commercial implications of influencer-driven food content.